1999
DOI: 10.1136/bjo.83.7.792
|View full text |Cite
|
Sign up to set email alerts
|

Creation and testing of a practical visual function assessment for use in Africa: correlation with visual acuity, contrast sensitivity, and near vision in Malawian adults

Abstract: Assessment of visual function by health workers may be a valuable tool in improving surgical uptake by encouraging both health personnel and patients to recognise that they have diYculties undertaking activities of daily living as well as a measure of monitoring and evaluating cataract outcomes. (Br J Ophthalmol 1999;83:792-795)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…At the time of interview, all patients had had at least 5 months and one opportunity to return to an outreach clinic in their vicinity. The audiotaped interview included a semistructured questionnaire to determine what steps the patients had taken since the outreach clinic in order to obtain money or a waiver for surgery, questions about their perceptions, needs and future plans for cataract surgery, and a visual function test designed for use in rural sub-Saharan Africa 8. At the conclusion of the interview the patient was given a waiver from the hospital that he could bring directly to the hospital or to the next outreach clinic to receive free surgery.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of interview, all patients had had at least 5 months and one opportunity to return to an outreach clinic in their vicinity. The audiotaped interview included a semistructured questionnaire to determine what steps the patients had taken since the outreach clinic in order to obtain money or a waiver for surgery, questions about their perceptions, needs and future plans for cataract surgery, and a visual function test designed for use in rural sub-Saharan Africa 8. At the conclusion of the interview the patient was given a waiver from the hospital that he could bring directly to the hospital or to the next outreach clinic to receive free surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Most vision-related QoL questionnaires were developed for use in high-income countries; fewer have been designed for use in developing countries. [17][18][19][20] Several studies have shown that there is a strong association between commonly measured visual acuity and scores in vision-related QoL questionnaires. [21][22][23] A decrease in visual acuity is likely to reduce QoL; however, other factors such as socio-demography (age, gender and socioeconomic status) and binocular status also have an important impact on QoL.…”
Section: S Briesen Et Almentioning
confidence: 99%
“…[21][22][23] A decrease in visual acuity is likely to reduce QoL; however, other factors such as socio-demography (age, gender and socioeconomic status) and binocular status also have an important impact on QoL. 17,18,20 We sought to determine the relative contribution of visual acuity, socio-demographic factors and vision-related QoL to acceptance of cataract surgery among a rural Kenyan population being provided free surgery.…”
Section: S Briesen Et Almentioning
confidence: 99%
“…This cut off was chosen because previous work in Malawi 8 had shown significant reductions in visual function at <6/60. The principal causes of blindness were grouped into causes related to lesions of the anterior segment, related to the lens, the posterior segment and related to the whole globe.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating the Chikwawa district data to the Malawi population reveals that the number of blind people has increased by 24%; the increase is primarily because of the large increase in the size of the most elderly group, aged 70 and above. Conclusion: The majority of blind people in Chikwawa (1983 and1999) are in the age group 70 and over. This group has had the largest proportional increase in population size in this time.…”
mentioning
confidence: 91%